Microparticles as Immune Regulators in Infectious Disease – An Opinion - Ling, Zheng L.; Combes, Valery; Grau, Georges E.; King, Nicholas J. (Frontiers in Immunology, 2011)
Despite their clear relationship to immunology, few existing studies have examined potential role of microparticles (MP) in infectious disease. Infection with pathogens usually leads to the expression of a range of inflammatory cytokines and chemokines, as well as significant stress in both infected and uninfected cells. It is thus reasonable to infer from studies to date that infection-associated inflammation also leads to MP production. MP are produced by most of the major cell types in the immune system, and appear to be involved at both the innate and adaptive levels, potentially serving different functions at each level. Thus, MP do not appear to have a universal function; instead their functions are source- or stimulus-dependent, although likely to be primarily either pro- or anti-inflammatory. Importantly, in infectious diseases MP may have the ability to deliver antigen to APC via the biological cargo acquired from their cells of origin. Another potential benefit of MP would be to transfer and/or disseminate phenotype and function to target cells. However, MP may also potentially be manipulated, particularly by intracellular pathogens for survival advantage.